Comprehensive analysis of the stability of tailings-geotextile composite—Iron Mine Tailings Dam in Gushan, Anhui, China - Zhou, Yuxin; Ji, Jinzhi; Hu, Xuelong; Hu, Shengsong; Wu, Xiaogang; Yuan, Canming; Zhu, Tianqiang (Frontiers in Earth Science, 2022)
The application of tailings-geotextile composites can effectively reduce tailings dam safety accidents. In this paper, the tailings dam of the Gushan Iron Mine is the research background. The construction of tailings-geotextile composites was briefly studied. Based on the existing experimental data, the permeability and physical properties of the composite material were analyzed, and the model of the composite material was generalized. The seepage characteristics of the composite were analyzed by using the numerical simulation method of the seepage field. Finally, the overall stability of the composite during the construction and storage phases was investigated. The conclusions are as follows: 1) In the early stage of stacking, the permeability coefficient of the composite body increases with the increase in filling tension; in the later stage, under the action of excess pore pressure, the composite body still exhibits strong permeability; 2) In the early stage of stacking, the height of the composite body is low, and the relative position of the saturated zone is relatively high; as the composite continues to rise or the stacking time increases, the lower part of the composite is gradually consolidated, and the position of the saturated zone is gradually raised; when the stacking is stopped, the saturated zone gradually decreases until it is close to the original position; 3) With the increase in the stacking height of the composite, the safety factor decreases rapidly; when the stacking height is 22.0 m, it decreases to the minimum; with time, the stability of the composite will gradually increase. This study helps people understand tailings-geotextile composites, and it has significant reference value for practical engineering.